Inositol-Limited Growth, Repair, and Translocation in an Inositol-Requiring Mutant of Neurospora crassa - Hanson, Barbara A. (1980)
The biochemical consequences of inositol limitation in an inositol auxotroph of Neurospora crassa have been examined as a means of disclosing the cellular role of inositol. The cellular levels of inositol in the inl mutant were proportional to the concentration of inositol in the growth medium whereas inositol phosphate levels remained relatively constant at about 0.1 μmol/g (dry weight). After 72 h of growth, about 57-fold more protein per milligram (dry weight) was released by the mutant grown on limiting inositol than by the inositol-supplemented control. When the inositol-limited growth medium was osmotically buffered with 1% NaCl, 3% NaCl, or 6% sorbitol, there was about 33, 74, or 54%, respectively, less protein released by the mutant. These results are consistent with cell lysis occurring in the mutant grown on limiting inositol because of a structurally weakened cell wall and membrane deterioration. When sufficient inositol for normal mycelial growth was supplied to an inositol-deficient mycelium, there was within 2 h a rapid incorporation of inositol to 85% of control levels. This incorporation occurred without significant growth by any area of the mycelium. About 10 to 15% of the total cell inositol was translocated forward from the older mycelial areas to the growing tips; only 2 to 5% of the total cell inositol was translocated backward toward the older mycelial areas. Possible mechanisms of translocation are discussed.